3D simulation of transient thermal-hydraulic characteristics in CEFR during emergency shutdown event. (November 2022) - Yin, Jing; Lu, Daogang; Zhao, Haiqi; Guo, Jinsong; Liu, Yizhe; Yang, Jun; Guo, Zhongxiao; Zhang, Yuhao
Abstract: Safe shutdown behavior of China Experimental Fast Reactor (CEFR) in emergency status is one of the key points in its safety assessment. The CEFR design incorporates a pool-type structure. However, the flow and heat transfer characteristics in the pool are complex, which results in obvious three-dimensional (3D) effects. Therefore, obtaining the 3D flow paths and accurate temperature distribution characteristics using a one-dimensional system code is difficult. In the present work, 3D computational fluid dynamics simulations were performed on the pool-type sodium-cooled fast reactor CEFR in full-scale. The "decoupling modeling and coupling calculation" method was used for performing numerical simulation to comprehensively investigate the 3D thermal and flow characteristics under emergency shutdown conditions. The convection and the corresponding heat transfer effects were evaluated by investigating both inter-flow and intra-flow paths in the reactor core. FLUENT 18.0 results were compared and verified with system code SELTAC simulation results. The results revealed that the residual heat was mainly dissipated by the intra-subassembly flow under reactor emergency shutdown conditions. The maximum core outlet temperature did not exceed 543.4 °C under emergency shutdown event, which is lower than the safety limit. This phenomenon indicates that if the heat-removal capability is maintained in the main heat exchange system, CEFR shutdown protection is effective. The three-dimensional results of the present work provide important numerical references for CEFR safety analysis.